Performance improvement using dynamic performance stubs - Peter Trapp; Christian Facchi (Fachhochschule Ingolstadt - University of Applied Sciences, 2007)
Dynamic Performance Stubs support performance improvement. They can be used to identify "hidden" bottlenecks and also to provide better estimations of the gain from performance improvement. The idea behind these stubbing mechanism will be described, the core concept will be explained and a closer look on the possibility of creating stubs will be given. Furthermore an introduction on "How to use dynamic performance stubs" is also included.
urn:nbn:de:bvb:573-292
Keywords: 650